Analisis Nyamuk Vektor Filariasis Di Tiga Kecamatan Kabupaten Pidie Nanggroe Aceh Darussalam - Fauziah Fauziah; Yekki Yasmin; Wira Dharma (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
The research about the trial of mosquitoes as the vector of filariasis which are endemic area of filariasis in three area district of Pidie have been done from August until Desember 2007. The aim of this research is to determinate and to know how the spesies of mosquitoes becoming the vector of filariasis in the endemic area in three area district of Pidie. The research was used the exploration methods and the taking of sample was done purposively. The result of the research was founded the larva in mosquito’s body, with the infection rate is 0,91%, and based on the result of identification that have been done, the mosquito is Culex quinquefasciatus. The result catching is also founded five kind of mosquitoes that have been reported as the natural vector of filariasis that are Culex annulirostris, Aedes aegypti, Anopheles subpictus, Anopheles barbirostris, and Anopheles vagus.